2015
DOI: 10.1186/s12885-015-1732-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Oct3/4 and Nanog in the head and neck squamous carcinoma cells and its clinical implications for delayed neck metastasis in stage I/II oral tongue squamous cell carcinoma

Abstract: BackgroundThe side population (SP) of cancer cells is reportedly enriched with cancer stem cells (CSCs), however, the functional role and clinical relevance of CSC marker molecules upregulated in the SP of head and neck squamous carcinoma (HNSCC) cells are yet to be elucidated. Patients with clinical stage I/II (T1-2N0M0) tongue squamous cell carcinoma (TSCC) typically undergo partial glossectomy; however, development of delayed neck metastasis (DNM) tends to reduce their survival. In the present study, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 84 publications
3
44
0
1
Order By: Relevance
“…[ [15][16][17][18] Etiological differences may have contributed to this result. In addition, majority of the tumors in the present study sample contained buccal mucosal cancers; while the literature quoted above have focused on tongue cancers.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[ [15][16][17][18] Etiological differences may have contributed to this result. In addition, majority of the tumors in the present study sample contained buccal mucosal cancers; while the literature quoted above have focused on tongue cancers.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, majority of the tumors in the present study sample contained buccal mucosal cancers; while the literature quoted above have focused on tongue cancers. [16,18] Furthermore, Sox-2 expression has been shown to be related to poor survival at sites such as esophagus and bladder as well. [19,20] In addition, problems highlighted below concerning survival data may have also contributed to this result.…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al reported their experience in providing effective and well-tolerated 0-7-21 palliative radiotherapy to patients with head and neck cancers [20].However,amongstageItonguecarcinomasthereisasubgroupoftumorsthatareprone tolymphnodemetastasisandlocalrecurrence.Ifthis more aggressive tumor behavior could be predicted,patientswhoareatincreasedriskoflymphnode metastasis and recurrence could be subjected to extendedtreatment,whereasthosewithlessaggressive carcinomas could be spared the morbidity associated with such treatment. Many attempts have been madetopredicttheoutcomefortonguecarcinomas throughhistopathologicstudiesandmolecularbiologyanalysis [21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SOX2 and NANOG have been reported to maintain quiescence programs in DTCs/residual cancer cells and may contribute to metastatic relapse (Sosa et al 2015). Although SOX2, NANOG, OCT4, and KLF4 have been shown to increase metastasis of bladder cancer, breast cancer, lung cancer, and head and neck squamous carcinoma cells (Celia-Terrassa et al 2012;Vaira et al 2013;Lu et al 2014;Habu et al 2015), none of these factors has been specifically studied during metastasis initiation. Based on current knowledge, it is tempting to speculate that these factors may also facilitate metastatic initiation by promoting cell plasticity, adaptability, survival, and self-renewal as they do in primary tumors.…”
Section: Cell Fate Determinants As Regulators Of Micsmentioning
confidence: 99%